2020
DOI: 10.1007/s10856-020-06448-9
|View full text |Cite
|
Sign up to set email alerts
|

Compositional dependence of the apatite formation ability of Ti–Zr alloys designed for hard tissue reconstruction

Abstract: Ti-Zr alloys are expected to be novel biomaterials with low stress shielding owing to their lower Young's moduli than pure Ti. The drawback of metallic biomaterials is that their bone-bonding abilities are relatively low. NaOH and heat treatments have been performed to provide Ti-50Zr with apatite-forming ability in the body environment, which is essential for bone bonding. However, the systematic compositional dependence of apatite formation has not been revealed. In the present study, NaOH treatment of Ti-Zr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The present results would be related to amount of surface functional group. We reported that amount of Ti-OH and Zr-OH groups in NaOH-treated Ti-50Zr was 75% of NaOH-treated Ti 5) . The adhesion of the apatite layer is also governed by the amount of the surface functional group.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The present results would be related to amount of surface functional group. We reported that amount of Ti-OH and Zr-OH groups in NaOH-treated Ti-50Zr was 75% of NaOH-treated Ti 5) . The adhesion of the apatite layer is also governed by the amount of the surface functional group.…”
Section: Discussionmentioning
confidence: 91%
“…Treatments of alloys based on NaOH and heating have been used to modify the surface of Ti-50Zr alloys. Such treatments may allow for partial apatite formation on the Ti-50Zr alloy surface after 7 days in a simulated body fluid (SBF), which has inorganic ion composition similar to that of extracellular fluid 4,5) . Ti-OH and Zr-OH groups formed on the alloy by the surface treatments are considered to trigger the heterogeneous apatite nucleation by a catalytic effect 3) .…”
Section: Introductionmentioning
confidence: 99%
“…In alkali-heating treatment [ 5 , 28 ], even after 7 d of SBF soaking, the apatite cannot cover the Zr-50Ti alloy completely. Additionally, the formed apatite was uneven and similar to those in group CaP, which were gigantic ball-like aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…Their elastic modulus is close to that of Zr-40Ti, the lowest among Zr-Ti binary alloys. The apatite-forming ability of Zr-Ti alloys significantly decreases when the Zr content exceeds 60 atom% [ 5 ]. These properties suggest that Zr-50Ti alloys could be a promising biomaterial.…”
Section: Introductionmentioning
confidence: 99%